HUBUNGAN KONFORMITAS DAN BUDAYA ORGANISASI DENGAN KINERJA GURU DENGAN KINERJA GURU SDN INTI DI KECAMATAN SIAK HULU - MUHAMMAD RIDHO; ISJONI ISJONI; DAENG AYUB NATUNA (Universitas Riau, 2017)
This study aims to reveal how good conformity, organizational culture, and teacherperformance and the relationship between conformity and the culture of the organization withthe performance of teachers. The population in this study are all teachers sector of JuniorSchool Inti In Siak Hulu Sub-District, the sampling technique using proportionate stratifiedrandom sampling. Data were collected using a questionnaire and analyzed descriptively bylooking at score of mean and inferential techniques korelasinonal. The results showed that: (1)conformity are at the category level is not good (2) organizational culture are at the categorylevel; (3) the performance of teachers at the level of either category. (4) there is a positive andsignificant relationship between conformity and teacher performance. (5) there is a positiveand significant relationship between organizational culture with teacher performance. (6) thereis a positive and significant relationship between culture oganisasi with teacher performance.Significantly conformity contributed 95.2% to the performance of teachers. The organizationalculture significantly contributed 93.8% to the performance of teachers. While conformity andorganizational culture simultaneously contributed 95.4% to the performance of teachers sectorof Junior School Inti In Siak Hulu Sub-District.